"Eavesdropping": An Information Source for Inpatients. Issue 12 (December 2020) - Beneteau, Erin; Haldar, Shefali; Mishra, Sonali R.; Pratt, Wanda
Abstract : Healthcare providers in the hospital setting must discuss patient information to ensure continuity of care and patient safety. This study explores how patients perceive the information they hear discussed between healthcare providers and how the concept of "eavesdropping" can be addressed by healthcare providers and in the field of medical informatics. Using an inductive analysis of interviews with 14 adult inpatients, research findings indicate that patients value receiving information in the hospital setting, including information received through eavesdropping. Patient eavesdropping opportunities include "eavesdropping by design" events, such as during bedside shift changes and handoffs, as well as unintended "unintended eavesdropping" events, such as listening to healthcare provider conversations outside of the patient's room. Healthcare providers and medical informaticists have opportunities to address eavesdropping in the inpatient setting. Informatics systems that address "eavesdropping by design" and "unintended eavesdropping opportunities" can improve patient-provider communication and satisfy patient preferences for receiving medical information.